ANTIK DAVR MANBALARIDA SALAVKIYLAR DAVLATI - O. Eshmamatova, Z. Eshimova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article talks about the establishment and development of the Seleucid state, as well as the social and economic development of the Seleucid state, which are continuously studied by historians.